Enhancing Students' Writing Skills on Short Functional Text Problem-Based Learning through Canva - Pujiyanti, Aminudin; Rokhayati, Titi; Widiyono, Yuli (Scripta : English Department Journal, 2024)
Writing is one of the skills that is quite challenging for students, especially middle school students. The aim of this study is to enhance the students` wiritng skill on Short Functional Text; Invitation Card. This study employed Classroom Action Research (CAR). The participants were students of class VIII D SMP N 1 Sukoharjo. The instruments used were observation, writing test, and questionnaires about students` responses. The results of this study showed that student’s ability in wiriting an invitation card still low before the application of Problem-Based Learning (PBL) method and Canva Application learning media and increase after the use of PBL and Canva application. Students also experience improvement in their ability to write invitation cards that is shown by the result of 96% percentage of achievement of learning objectives.